Circular Economy Strategies for Resource Efficiency and Sustainable Development in Manufacturing Industries - Balaji, S G; Reddy Penubaka, Kiran Kumar; Kumar, Munish; Goel, Priyanka; Jadhav, Aniket B.; Mohakud, Sujata (Journal of Neonatal Surgery, 2025)
The focus of this research is on the use of Circular Economy (CE) strategies for promoting sustainable development as well as improvement of manufacturers’ resource efficiency. The study adopts a comprehensive methodology framework of experimental analysis and Comparative evaluation and presents how CE has applied its impact in the area of manufacturing operations transformation. Improvements in both environmental and operational performance were observed through implementation of waste minimization practices, product life cycle extension as well as resource recovery systems. Experimental results showed that the CE integrated manufacturing setups were associated with a reduction in material waste of about 35%, significant increase in resource efficiency by 28%, and improvement by at least about 40% in energy utilization as compared to traditional linear models. Moreover, product reuse and remanufacturing were increased by 45%, emissions of carbon reduced by 32 percent. The results also compared favorably with existing models and literature related to it and showed the potential of CE frameworks for changing industrial practices to deliver better sustainability outcomes. The importance of integrating smart technologies, involving stakeholder collaboration, and support from policy is stressed in this study and the importance of facilitating the adoption of circular models across the board. In the end, the research has added to the ongoing discussion on sustainable industrial transformation and offers actionable insights to industries who want to adapt to global sustainability goals.